Addition of nanomer clays to GFRPs for enhanced impact strength and fracture toughness. (31st August 2018) - Shelly, Daksh; Singh, Karanbir; Nanda, Tarun; Mehta, Rajeev
Abstract: The influence of reinforcement of two different nano-clays, an un-modified clay (Nanomer ® PGV) and an organically modified clay (Nanomer ® I.28E) on the impact strength, tensile properties, fracture toughness, and flexural properties of epoxy based glass fiber reinforced polymer (GFRP) clay nanocomposites was investigated. GFRPs were fabricated using vacuum assisted resin infusion moulding (VARIM) technique. Exfoliated/intercalated nano-clay morphologies were obtained in all the processed nanocomposites. The mechanisms for improvement/change in properties were corroborated with the help of SEM/TEM analysis and x-ray diffraction patterns. Interestingly, greater improvement in mechanical performance was observed for nanocomposites reinforced with unmodified nano-clay as compared to organically modified nano-clay. Maximum improvement of 22%, 31%, and 73% was observed in impact strength, flexural strength, and fracture toughness respectively over the reference sample i.e. GFRP without nano-clay.